Pengaruh Disiplin Kerja dan Kompetensi Kerja Terhadap Kinerja Pegawai di Kantor Kecamatan Gerokgak - Candra Muhammad Fadilla; M. Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
This study aims to examine the effect of work discipline and work competence on employee performance at the Gerokgak District Office. The population of this study consists of all employees at the Gerokgak District Office. The sampling technique used is non-probability sampling with a saturated sampling approach, in which all employees are included as respondents. The sample size in this study comprises employees who meet the research criteria. The research method employed is a causal quantitative approach. Data were collected through the distribution of questionnaires that were tested for validity and reliability. Data analysis was conducted using SPSS version 21 for Windows. The results indicate that: (1) work discipline has a positive and significant effect on employee performance, (2) work competence has a positive and significant effect on employee performance, and (3) work discipline and work competence simultaneously have a positive and significant effect on employee performance at the Gerokgak District Office. These findings emphasize that the combination of good work discipline and adequate work competence can optimally enhance employee performance.